Iron-Binding Capacity and Antidiabetic Activity of Baby Clam (Corbiculidae sp.) Meat Protein Hydrolysate - Vo, Tam Dinh Le; Huynh, Thu; Le, Thuy Thi; Tran, An Thi Tuong; Vo, Bao Chi (Universitas Gadjah Mada, 2025)
Baby clam (Corbiculidae sp.) meat is served as a traditional dish in Vietnam, and the antioxidant activity of its protein extract has been discovered. This study evaluates baby clam meat protein hydrolysate's iron-binding capacity (IBC) and antidiabetic activity. Initially, an analysis of the basic chemical composition of the meat was conducted. Subsequently, Alcalase was employed for hydrolysis. The highest IBC and α-amylase inhibition activity were targets for obtaining the best hydrolysis condition, including the clam meat-to-water ratio, enzyme-to-substrate (E:S) ratio, and time. Under the best condition, the hydrolysates demonstrated the IBC of 1246.20 ± 44.00 µg Fe2+/g protein and α-amylase inhibition activity of 48.33 ± 1.44%, approaching three-quarters of the activity of ethylenediaminetetraacetic acid (EDTA) sodium salt and acarbose, respectively. These results served as preliminary data for the development of the protein hydrolysates as a natural iron chelator or α-amylase inhibitor, which could support the treatment of iron deficiency and diabetes.